Autonomic dysfunction in Parkinson’s disease - Pfeiffer, Ronald (Henry Stewart Talks, 2015)
Cardiovascular dysfunction (Denervation, Orthostatic hypotension), Gastrointestinal dysfunction (Excess saliva, Dysphagia, Gastroparesis, Small intestinal dysfunction, Bacterial overgrowth, Bowel dysfunction, Constipation, Defecatory dysfunction, Anorectal testing), Urinary dysfunction (Irritation, Obstruction), Sexual dysfunction, Thermoregulatory dysfunction (Hyperthermia/Hypothermia, Dyshidrosis, Hyperhidrosis)